PENGARUH SUHU HEAT MOISTURE TREATMENT (HMT) TERHADAP KARAKTERISTIK FISIKOKIMIA PATI TALAS BENENG - Wulandari, Puji; Vega Yoesepa Pamela; Abidin Mustofa; Ghasany Taqiyya Salsabila Zulafa Iskandar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Heat-moisture treatment (HMT) is known as one of physical modiﬁcation techniques that improves the functional property of starch. Taro beneng starch isolated from taro beneng tuber was modified by HMT to improve its application in the food product. The aim of this research is to determine the physical and functional properties of taro beneng starch modified by HMT. HMT were applied to the taro beneng starch using three different temperatures (90,100, and 100oC). This research was conducted using a randomized-complete design. The results showed that the temperature did not had a significant effect on the whiteness degree and lightness, however had a significant effect on the resistant starch content and flowability of the modified starch. Future studies about its effect on the nutritional and crystallinity characteristics of this starch need to be done to provide a better understanding of the implications of this technique.